Evaluation of Fermentation on Moringa Leaves (Moringa oleifera) as Raw Material on Feed of Tilapia (Oreochromis niloticus) ) - Achmad Noerkhaerin Putra; Citra Widia Ningsih; Fitriana Sari Nurani; Mustahal Mustahal; Forcep Rio Indaryanto (Jurnal Perikanan dan Kelautan, 2018)
Moringa leaves is a potential ingredient for raw material of tilapia feed, which a high protein content of 25%. However, moringa leaves has a high fibre and antinutritional factors. The aims of this study was to evaluate the fermentation of Moringa leaves (Moringa oleifera) as a raw material feed on tilapia (Oreochromis niloticus). This study was conducted for eight months at Laboratory of Aquaculture, Department of Fisheries, Faculty of Agriculture, University of Sultan Ageng Tirtayasa. The study consisted of 4 treatments of feed with different fermentations, namely: A: reference feed 70% + Moringa leaves meal 30%, B: reference feed 70%+fermented Moringa leaves meal with Rhizopus oligosporus 30%, C: reference feed 70%+fermented Moringa leaves meal with Saccharomyces cereviceae 30%, and feed D: reference feed 70%+fermented Moringa leaves meal with Aspergillus niger 30%. The results showed that feed with Moringa leaves fermentation using A. niger resulted in the best growth on tilapia compared to other treatments. Fermentation with A. niger and R. oligosporus on Moringa leaves produced the best nutrient digestibility value compared to other treatments. Moringa leaves fermented with A. niger, S. cerevisiae and R. oligosporus had no effect on physiological processes on tilapia, as shown by hematological parameter values that were within the normal range. Moringa leaves fermented with Aspergillus niger can be used as a raw material for tilapia feed.